ANALYZING THE ROLE OF BUZZ MARKETING ON START-UP CULLINARY BUSINESS IN MANADO - Tangel, Lois Merry; Tulung, Joy E.; Tielung, Maria V.J. (Universitas Sam Ratulangi, 2019)
Abstract:Buzz Marketing refers to marketing strategies used to capture the attention of the customers and other influencers to amplify the marketing message to an extent where talking about the brand, product, or service becomes entertaining, fascinating, and newsworthty also word of mouth marketing. The aim of this study is to know how is the Role of Buzz Marketing on Start-Up Cullinary Business in Manado. In order to achieve these objectives the researcher got information from 10 respondents using qualitative study which is in-depth interview and uses purposive sampling. The results show that Buzz Marketing has played Â an important role for the Start-Up Cullinary Business, and it has given a positive impact to their business. All the informants said that Buzz Marketing was very helpful and useful for promoting and offering a product of cullinary business. Through Buzz Marketing it is easy for the Owners of Cullinary Business to promote their productsÂ and it is very easy, low cost with high impact. The recommendation for the Start-Up Cullinary Business, it is good to keep using Buzz Marketing to promote their product, so their product will grow up faster and be known by many people, in addition they still need to keep it improving and sustain.Â Keywords: buzz marketing, start-up business, cullinary business.